PENGARUH PENUNDAAN WAKTU TERHADAP HASIL URINALISIS SEDIMEN URIN - Naid, Tadjuddin; Mangerangi, Fitriani; Almahdaly, Hanifah (Jurnal Ilmiah As-Syifaa, 2014)
A research about the effect of time delays on the result of urinalysis urine sediment. This research is aimed to determine the presence or absence effect of delay on the result of urine sediment eximination. This research used cross sectional study. Total amount sample was 37 samples and using urine at the time. A microscopic examination of a sample ( urine sediment) by the method of Shih-Yung. The research result showed that the average number of leukocytes in immediate examination, 2 hour, amd 3 hour are 1,29/µl, 1.05/µl, 0,89/ µl respective, the average numberof erythroctes immediate examination,2 hour, and 3 hour are  0,70/ µl, 0.59/ µl, 0,48/µl, respective, the average number of epitheliel cell examination immediate, 2 hour, and 3 hour are 9,70/LPB, 8,51/LPB, 7,54/LPB respective. By One Way Anova statistical Test, test value P>0,05 with a value of F count < F table. Based one data the result of study then it can be conclusion that are no signifikan effect of time delay urine sediment examination immediate, 2 hours and 3 hours at room temperature.Key words: Time, Urinalisis, Urin.